Enhancing Energy Efficiency In Moroccan Industry: The Role Of Energy Audits (Journal of Namibian Studies : History Politics Culture, 2023)
This short report presents a summary derived from an original research titled “Energy Audit as an Instrument to Tackle Internal Barriers to Energy Efficiency: Lessons from Moroccan Industrial Firms”. The main objective of the research was to explore the effect of energy audits on addressing internal barriers to energy efficiency within industrial companies in Morocco. The research uncovered significant findings regarding the benefits of energy audits, and implications for both policymakers and researchers. This short report discusses the method, the existing literature, the results, outlines the limitations and suggests avenues for further research. By offering a condensed overview of original study, this report is a readily available for research interested in the importance of energy audits in promoting energy efficiency practices.